(untitled) (Research, Society and Development, 2024)
The objective of this study was to describe the importance of nursing care during prenatal care for pregnant adolescents. This is an integrative literature review research carried out between the months of June and July 2023. The PICo strategy was used, where P (population) corresponds to adolescents; o I (interest), nursing care and Co (context), prenatal care. The search was carried out in the database of the Medical Literature and Retrivial System onLine (MEDLINE/PubMed), Latin American and Caribbean Literature on Health Sciences Information (LILACS) and the Nursing Database (BDENF), the descriptors The controlled variables used in the search strategy were selected from DeCs (Health Sciences Descriptors), using the Boolean connectors AND and OR. 18 (eighteen) articles were found, an exploratory reading of them was carried out, of which 08 (eight) were excluded, for the present research 10 (ten) articles were used. The results of the study showed that the role of the nurse is of great relevance during prenatal care, as they carry out specific technical activities within their competence, administrative and educational and, through the bond with users, concentrate efforts to reduce taboos, myths and prejudices and seek conviction about the main care during pregnancy.